PRICE AND PROMOTION INFLUENCE ON THE DECISION TO PURCHASE A MOTORCYCLE AT HONDA TUNAS DEALER DWIPA MATRA - Jaka Adi Yantara; Irsandi; Trenggono Pujo Sakti; Suci Asfaranin (ZILLZELL MEDIA PRIMA, 2025)
This study investigates the impact of pricing and promotional strategies on motorcycle purchasing decisions at the Honda Tunas Dwipa Matra dealership. A quantitative research methodology was utilized for this analysis. Data were gathered through questionnaires distributed to customers who had made purchases at the dealership. The sample size was calculated using Slovin's formula, allowing for a 15% margin of error, resulting in a total of 45 respondents. Data analysis was performed using multiple linear regression with SPSS version 30. The findings reveal that the t-value for price is 2.465, which exceeds the critical t-value of 2.016, with a significance level of 0.018. Furthermore, the t-value for promotion is 2.264, also surpassing the critical t-value of 2.016, with a significance level of 0.029. These results indicate that both price (X1) and promotion (X2) have a significant effect on motorcycle purchasing decisions (Y) at the Honda Tunas Dwipa Matra dealership.